Complementary sources of financing cultural institutions – economic activity (services, trade, property management), investment of free funds and sponsorship - Bartosz Kołaczkowski; Małgorzata Ratajczak (Prawo Budżetowe Państwa i Samorządu)
This article is focused on sources of financing for cultural institutions, for which the Authors recognize economic activity (services, trade, property management), allocating free funds and sponsorship. The text is narrowed to sources of financing which supplement subsidies. Considerations in individual parts of this article intend to answer the following questions: can these funds constitute a significant source of financing for cultural institutions? Is the legal regulation concerning these funds transparent enough to make their effective use trouble-free for the people managing these institutions? Could these funds offset the financial impact of a pandemic, and perhaps even replace the primary source of funding for culture, such as subsidies? The authors show that the above-mentioned supplementary sources of financing for cultural institutions may constitute important sources of financing for cultural activities. However, these funds absolutely do not release the state and local governments from their obligation to take care of the development of Polish culture, and in most cases these funds will not offset the negative financial effects of the pandemic. In addition, the legal regulation concerning them is scattered and sometimes excessively complicated.